School Management as a School Mover in Realizing Educational Transformation - Luthfillah, Ananda; Widayatsih, Tri; Mahasir, Mahasir (PPSDP International Journal of Education, 2025)
This study focuses on the management of school mover in realizing educational transformation (case study at SD Az-Zahrah Palembang), which aims to determine the planning, organization, implementation, and organization of supervision of school mover in realizing educational transformation. This study uses a qualitative approach with the case study method. School mover are catalysts for realizing the vision of Indonesian education, namely realizing a sovereign, independent, and personality-based advanced Indonesia through the creation of Pancasila students. School mover focus on developing student learning outcomes holistically by realizing the profile of Pancasila students that includes competencies and characters that begin with superior human resources (principals and teachers).